Microclimate: A critical review in the context of pressure ulcer prevention. (November 2018) - Kottner, Jan; Black, Joyce; Call, Evan; Gefen, Amit; Santamaria, Nick
Abstract: Pressure ulcers are caused by sustained mechanical loading and deformation of the skin and subcutaneous layers between internal stiff anatomical structures and external surfaces or devices. In addition, the skin microclimate (temperature, humidity and airflow next to the skin surface) is an indirect pressure ulcer risk factor. Temperature and humidity affect the structure and function of the skin increasing or lowering possible damage thresholds for the skin and underlying soft tissues. From a pressure ulcer prevention research perspective, the effects of humidity and temperature next to the skin surface are inextricably linked to concurrent soft tissue deformation. Direct clinical evidence supporting the association between microclimate and pressure ulceration is sparse and of high risk of bias. Currently, it is recommended to keep the skin dry and cool and/or to allow recovery periods between phases of occlusion. The stratum corneum must be prevented from becoming overhydrated or from drying out but exact ranges of an acceptable microclimate are unknown. Therefore, vague terms like 'microclimate management' should be avoided but product and microclimate characteristics should be explicitly stated to allow an informed decision making. Pressure ulcer prevention interventions like repositioning, the use of special support surfaces, cushions, and prophylactic dressings are effective only if they reduce sustained deformations in soft tissues. This mode of action outweighs possible undesirable microclimate properties. As long as uncertainty exists efforts must be taken to use as less occlusive materials as possible. There seems to be individual intrinsic characteristics making patients more vulnerable to microclimate effects. Highlights: An object on the skin surface provides an impedance to convective heat loss. An object on the skin surface provides an impedance to evaporative moisture loss. Microclimate is an effect-modifier or an indirect risk factor for pressure ulcer development. Effects of 'microclimate interventions' on pressure ulcer prevention are unclear. The term 'microclimate management' should not be used.